Analysis of the correlation between BMI and respiratory tract microbiota in acute exacerbation of COPD - Cao, Yang; Chen, Xiaolin; Shu, Lei; Shi, Lei; Wu, Mingjing; Wang, Xueli; Deng, Kaili; Wei, Jing; Yan, Jiaxin; Feng, Ganzhu (Frontiers in Cellular and Infection Microbiology, 2023)
Objective To investigate the distribution differences in the respiratory tract microbiota of AECOPD patients in different BMI groups and explore its guiding value for treatment. Methods Sputum samples of thirty-eight AECOPD patients were collected. The patients were divided into low, normal and high BMI group. The sputum microbiota was sequenced by 16S rRNA detection technology, and the distribution of sputum microbiota was compared. Rarefaction curve, α-diversity, principal coordinate analysis (PCoA) and measurement of sputum microbiota abundance in each group were performed and analyzed by bioinformatics methods. Results 1. The rarefaction curve in each BMI group reached a plateau. No significant differences were observed in the OTU total number or α-diversity index of microbiota in each group. PCoA showed significant differences in the distance matrix of sputum microbiota between the three groups, which was calculated by the Binary Jaccard and the Bray Curtis algorithm. 2. At the phylum level, most of the microbiota were Proteobacteria, Bacteroidetes Firmicutes, Actinobacteria, and Fusobacteria. At the genus level, most were Streptococcus, Prevotella, Haemophilus, Neisseria and Bacteroides. 3. At the phylum level, the abundance of Proteobacteria in the low group was significantly higher than that in normal and high BMI groups, the abundances of Firmicutes in the low and normal groups were significantly lower than that in high BMI groups. At the genus level, the abundance of Haemophilus in the low group was significantly higher than that in high BMI group, and the abundances of Streptococcus in the low and normal BMI groups were significantly lower than that in the high BMI group. Conclusions 1. The sputum microbiota of AECOPD patients in different BMI groups covered almost all microbiota, and BMI had no significant association with total number of respiratory tract microbiota or α-diversity in AECOPD patients. However, there was a significant difference in the PCoA between different BMI groups. 2. The microbiota structure of AECOPD patients differed in different BMI groups. Gram-negative bacteria (G-) in the respiratory tract of patients predominated in the low BMI group, while gram-positive bacteria (G+) predominated in the high BMI group.